A SATISFIED READER - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Mathieu Idiawo, N'gaoundere, Cameroon: 'Thanks to items published by you I won the first prize award by APICA for the best dissertation written about development. My idea was to carry out my own research on training rural people. '